Asymmetric NaBH4 1, 4‐Reduction of C3‐Disubstituted 2‐Propenoates Catalyzed by a Diamidine Cobalt Complex. Issue 10 (27th April 2015) - Shuto, Yoshihiro; Yamamura, Tomoya; Tanaka, Shinji; Yoshimura, Masahiro; Kitamura, Masato
Abstract A new Co complex of a unique diamidine ligand catalyzes asymmetric NaBH4 reduction of C3‐disubstituted (E)‐ and (Z)‐2‐propenoates, including C3‐oxygen‐ and nitrogen‐substituted substrates with high enantioselectivity. Analysis by X‐ray diffraction, 1H NMR spectroscopy, ring‐opening radical‐clock and D‐labeling reactions, and the structure/selectivity relationship suggest that a mechanism of CoH‐involved non‐single‐electron transfer 1, 4‐addition differentiates the C2 enantioface. Involvement of CoH species has been supported by quantitative isolation of a new type of CoH2(BH3)2 complex.